Fraud under the Civil and Commercial Code or fraud under the Penal Code: a study of similarities and differences within the context of Thai law. - nali, Phramahasuthon (Law for Development Graduate Journal, 2025)
This article aims to compare fraud under the Civil and Commercial Code or fraud under the Penal Code under the Thai legal system. While both involve deceptive practices and require intention, there are several significant differences. Civil fraud focuses on protecting the purity of intention in juristic acts and results in voidable contracts, whereas criminal fraud has a broader scope, aims to protect property rights, and punishes offenders without requiring the existence of a juristic act. Furthermore, they differ in their procedural aspects and remedies, with civil fraud utilizing civil proceedings and focusing on damage compensation, while criminal fraud employs criminal proceedings with penal sanctions. In civil fraud, the burden of proof is based on the preponderance of evidence, whereas criminal fraud requires proof beyond reasonable doubt. Civil fraud is confined to contractual relationships, while criminal fraud encompasses a wider range of fraudulent activities. This comparative study of similarities and differences between civil and criminal fraud contributes to a better understanding of both legal principles.